Implementation of Social Forestry Policy on Fulfillment of Empowerment Rights of Women Family Heads in Gaining Access to Forest Management in Sabrang Ambulu - Juwianti, Ari; Adawiyah, Putri Robiatul (Indonesian Journal Publisher, 2024)
This study aims to demonstrate that the Social Forestry Program in Sabrang Village positively impacts poverty alleviation and community welfare, particularly among women family heads, through forest land management. This study employed a descriptive qualitative data analysis strategy. This research method uses the purposive sampling strategy. The findings of this study show that the realization of women's rights can already be felt and benefited. Forest land management activities are carried out through the social forestry initiative to maximize natural resource potential over 35 years. As a result, it may be argued that it successfully changed the community's economics, particularly that of women's household heads.